2022 Excellence in Refereeing (Journal of Accounting Research, 2023)
The Journal of Accounting Research is proud to recognize our top referees of the previous calendar year. The senior editors selected those named below for their “2022 Excellence in Refereeing” based on the quality and the number of reviews they had performed for the journal during the 2022 calendar year. We thank the referees for their invaluable services to the journal. Jannis Bischof, University of Mannheim Matthew Bloomfield, University of Pennsylvania Pietro Bonetti, IESE Business School Thomas Bourveau, Columbia University Mark Bradshaw, Boston College Matthias Breuer, Columbia University Jung Ho Choi, Stanford University Yiwei Dou, New York University Raphael Duguay, Yale University Travis Dyer, Brigham Young University Henry Eyring, Duke University Fabrizio Ferri, University of Miami Henry Friedman, University of California, Los Angeles Stephen Glaeser, University of North Carolina João Granja, University of Chicago Nicholas Guest, Cornell University Steven Kachelmeier, University of Texas, Austin John Kepler, Stanford University Sehwa Kim, Columbia University Ranjani Krishnan, Michigan State University Lian Fen Lee, Boston College Miao Liu, Boston College Yao Lu, Cornell University Daniele Macciocchi, University of Miami Charles McClure, University of Chicago Mihir Mehta, University of Michigan Maximilian Muhn, University of Chicago James Omartian, University of Michigan Gaizka Ormazabal, IESE Business School Hong Qu, Kennesaw State University Thomas Rauter, University of Chicago Delphine Samuels, University of Chicago Timothy Shields, Chapman University Nemit Shroff, MIT Lorien Stice-Lawrence, University of Southern California Stephen Stubben, University of Utah Andrew Sutherland, MIT Sorabh Tomar, Southern Methodist University Rahul Vashishtha, Duke University Felix Vetter, University of Mannheim Dushyantkumar Vyas, University of Toronto Charles Wang, Harvard Business School Clare Wang, University of Colorado, Boulder Edward Watts, Yale University TJ Wong, University of Southern California Gaoqing Zhang, University of Minnesota Frank Zhou, University of Pennsylvania Christina Zhu, University of Pennsylvania Luo Zuo, Cornell University